IMPROVING THE METHODOLOGY OF ANALYSIS AND EVALUATION OF FINANCIAL RESULTS OF AGRICULTURAL ENTERPRISES - Mirzayev Umidjon Mirzakhmedovich (Modern American Journals, 2025)
This article is devoted to the analysis and improvement of the methodology for evaluating the financial results of agricultural enterprises. The study highlights the theoretical foundations of financial result analysis, identifies the limitations of traditional methods, and examines the specific features of agriculture such as seasonality, climatic risks, and long production cycles.
Keywords: Agriculture, financial results, profitability, revenue, costs, analysis, methodology, Uzbekistan, risk management.